Analysis of metacognition difficulties in problem-solving static fluid material in term of Hippocrates â€“ Galenus personality type - Eni Setyawati; Susilawati Susilawati; Dwi Sulisworo (Indonesian Review of Physics (IRiP), 2019)
Describing student's metacognition difficulties and thinking the process in problem-solving static fluid material in each melancholic, sanguinic, phlegmatic, and choleric (Hippocrates - Galenus) personality type. This data analysis method uses a Likert scale as a measurement scale. The data analysis technique used was grouping data into four categories: Understanding The Problem, Devising A Plan, Carrying Out The Plan, Looking Back. The cause of students' metacognition difficulties caused by a lack of understanding the concept of physics, knowing symbols, formulations, notations, and calculations that will be done in each problem solving, and lack of understanding strategies in problem-solving. Students who had a melancholic, sanguinic, choleric personality type were students who had metacognition difficulties when understanding and solving the problem, and also had problems in considering strategies and realizing the use of using strategy. Students who had the Phlegmatic personality type were able to understand the problem by looking at the problem and then making an image so that it can change the information into the form of physics.Â Â